Peran Pondok Pesantren Gadingmangu Terhadap Kesejahteraan Dan Akhlak Masyarakat Desa Gadingmangu Kecamatan Perak Kabupaten Jombang - Anita Choyrina; Adibah Jauhari; Abdul Rouf (Arsy : Jurnal Studi Islam, 2018)
The objective of this research is to find the role of boarding schools for the welfare and morals Gadingmangu rural districts Gadingmangu Perak Jombang district. This study aims to describe and analyze critically about the role of boarding schools for the welfare and morals Gadingmangu rural districts Gadingmangu Perak Jombang district. This research is a quantitative approach with descriptive methods, taking a boarding school Gadingmangu background and Gadingmangu the villagers participated in a boarding school. The data collection is done by conducting observations, documentations and equipped for the study of literature. The data were analyzed using descriptive formula percentage and SPSS version 18 for windows. The results showed: Gadingmangu boarding school was instrumental to the welfare and morals rural districts Gadingmangu Perak Jombang district. Indicated by the results of output SPSS version 18 with mean 28,03, minimum 24 and maximum 30, with a standard deviation 1,532 and skewness and kurtosis respectively -,674 and 0,094 which means that the role of boarding school Gadingmangu to the welfare and morals rural districts Gadingmangu Perak Jombang district normally distributed.